Debridement, interbody graft using titanium mesh cages, posterior instrumentation and fusion in the surgical treatment of multilevel noncontiguous spinal tuberculosis in elderly patients via a posterior-only. Issue 2 (February 2017) - Wang, Yu-Xiang; Zhang, Hong-Qi; Li, Min; Tang, Ming-xing; Guo, Chao-feng; Deng, Ang; Gao, Qile; Wu, Jian-Huang; Liu, Jin-Yang
Abstract: Purpose: To analyse the efficacy and feasibility of surgical management for elderly patients with multilevel non-contiguous spinal tuberculosis(MNSTB)by using one-stage posterior focus debridement, interbody graft using titanium mesh cages, posterior instrumentation and fusion. Methods: From September 2009 to October 2013, 15 elderly patients with MNSTB were treated with one-stage posterior focus debridement, interbody graft using titanium mesh cages, posterior instrumentation and fusion. There were 10 males and 5 females with a mean age of 63.2 years (range: 60–68 years) at the time of surgery. The mean follow-up time was 40 months(range 26–68 months). Patients were evaluated before and after surgery in terms of erythrocyte sedimentation rate(ESR), neurological status, pain and kyphotic angle. Results: The spinal tuberculosis was completely cured, and the grafted bones were fused in all 15 patients. There were no recurrent tuberculous infections. The ESR reached a normal level within 3 months in all patients. The ASIA neurological classification improved in all cases, and pain relief was reported by all patients. The average preoperative kyphosis was 20.1° (range 8–38°) and decreased to 7.6° (range 1–18°) postoperatively. There was no significant loss of the correction at the latest follow-up. Conclusions: Our results showed that one-stage posterior focus debridement, interbody graft using titanium mesh cages, posterior instrumentation and fusion was an effective treatment for elderly patients with MNSTB. It is characterized by minimum surgical trauma, good neurological recovery, and good correction of kyphosis.